Psikoedukasi Tentang Risiko Perkawinan Usia Muda untuk Menurukan Intensi Pernikahan Dini pada Remaja - Maulida Rahmah; Zainul Anwar (JIP (Jurnal Intervensi Psikologi), 2015)
Various reasons for a person doing early marriage, one of which is a condition where a person who has a strong desire to be married at a young age or who can be called with the intention. Intentions early marriage is the tendency of a marriage that has the desire to get married at the age of adolescence or under the age of 20 years. Increased intentions early marriage can be resolved, either by providing psychoeducation. The purpose of this study was to investigate the effect of psychoeducation early marriage in reducing early marriage intentions in adolescents in South Borneo. The research subjects were followed psychoeducation by category amounted to 55 people. This study is a quasi experimental study (quasi) also called quasi-experiment which is resembling (similar). This research uses a method of pre-experimental design with a kind of pre-test and post-test one group design. This method is given to one group without a comparison group. The results showed there were significant differences in scores on treatment without psychoeducation and with the treatment given psychoeducation t (-39,305; p = 0.000 <0.05). Thus, we can conclude that psychoeducation may be used to reduce early marriage intentions. Keywords: Psychoeducation, intentions early marriage, teenage